2014
DOI: 10.1597/13-045
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bone Volume after Secondary Bone Grafting in Unilateral Alveolar Cleft Using Computer-Aided Engineering

Abstract: The purpose of this study was to evaluate the initial defect and the outcome of bone grafts for unilateral alveolar cleft. To determine the absorption of the bone graft in patients with unilateral cleft, computer-aided engineering (CAE) with multi-detector row computed tomography (MDCT) was used. MDCT scans of 29 patients were taken immediately preoperatively and at 1 month and 6 months postoperatively. The patients underwent bone grafting between 8 and 14 years of age using iliac crest bone grafts. Three-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 18 publications
0
27
0
2
Order By: Relevance
“…Of the nine clinical studies analyzed, three reported inclusion of patients under the age of 9 and three included patients aged >12 years . Five of the studies in the sample included patients aged 9–12 years .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the nine clinical studies analyzed, three reported inclusion of patients under the age of 9 and three included patients aged >12 years . Five of the studies in the sample included patients aged 9–12 years .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies included patients with bilateral clefts , whereas six included patients with unilateral clefts .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 Computer-aided surgical designs improve the accuracy and effectiveness of surgeries. It is not possible to surgically correct all deformities present in oblique facial clefts.…”
mentioning
confidence: 99%